Effect of graphene nanoplatelet addition on properties of thermo-responsive shape memory polyurethane-based nanocomposite. Issue 4 (2nd April 2016) - Kausar, Ayesha; Ur Rahman, Amin
ABSTRACT: Graphene nanoplatelet (GNP) was added as reinforcement to novel blend of polyurethane (PU) and poly(ethylene-co-ethyl acrylate-co-maleic anhydride) (PEEAMA) with an intended application for heat-induced shape recovery. Objective of the study was to explore the effect of GNP addition on morphology, mechanical properties, and heat-induced shape recovery. Physical inter-linking of GNP platelets to blend components directed unique self-assembled pattern. Neat blend revealed gyroid morphology while addition of functional GNP initiated well-defined double gyroid pattern on folds of primary gyroid structure. At a concentration of 5 wt.% GNP, the nanocomposite film showed highest improvement in tensile strength (54%) and Young's modulus (57%) as compared to blend. The nanocomposite samples showed shape recovery phenomenon at Tm (60°C). In 5 wt.% GNP-loaded nanocomposite, the original shape of samples was nearly 96% recovered within 7 s.